2015
DOI: 10.1111/cdoe.12180
|View full text |Cite
|
Sign up to set email alerts
|

Community water fluoridation and health outcomes in England: a cross‐sectional study

Abstract: This study uses the comprehensive data sets available in England to provide reassurance that fluoridation is a safe and highly effective public health measure to reduce dental decay. Although lower rates of certain nondental outcomes were found in fluoridated areas, the ecological, observational design prohibits any conclusions being drawn regarding a protective role of fluoridation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…The finding of a 46% lower PPDH rate in 0- to 4-y-olds living in fluoridated compared to nonfluoridated postcodes, when adjusting for SES, is similar to that reported in recent studies. In England, lower dental hospitalization rates of 45% and 55%, when adjusting for deprivation, were found in 1- to 4-y-olds living in fluoridated areas compared to nonfluoridated areas (Public Health England 2014; Young et al 2015). In addition, Klivitsky and colleagues (2015) found a 53% lower dental hospitalization rate in 0- to 18-y-olds living in fluoridated compared to nonfluoridated Israeli cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of a 46% lower PPDH rate in 0- to 4-y-olds living in fluoridated compared to nonfluoridated postcodes, when adjusting for SES, is similar to that reported in recent studies. In England, lower dental hospitalization rates of 45% and 55%, when adjusting for deprivation, were found in 1- to 4-y-olds living in fluoridated areas compared to nonfluoridated areas (Public Health England 2014; Young et al 2015). In addition, Klivitsky and colleagues (2015) found a 53% lower dental hospitalization rate in 0- to 18-y-olds living in fluoridated compared to nonfluoridated Israeli cities.…”
Section: Discussionmentioning
confidence: 99%
“…Australian studies have shown that child PPDH rates are associated with low socioeconomic status (SES) (Department of Human Services [DHS] 2007; Rogers and Morgan 2012; Butler et al 2013), no access to community water fluoridation (CWF) (DHS 2007), and residence in geographically remote locations where there is limited availability of oral health professionals (OHPs) (AIHW 2016a). The impact on child DGAs of CWF and SES has been shown in 3 published studies: in Israel among under 18-y-olds (Klivitsky et al 2015) and in studies in England among under 5-y-olds (Public Health England 2014; Young et al 2015). These studies did not focus on PPDHs or control for availability of dental care.…”
Section: Introductionmentioning
confidence: 97%
“…Such surveillance 19 has also been recommended in other countries including Australia, New Zealand, the USA, Canada, Israel and England. 20,21 In all of these countries, scientifically robust evaluations have been made and published, recording the continued effectiveness of water fluoridation. These are cross-sectional studies, which have compared the caries experience of people, of various ages, with a history of exposure, partial exposure, or no exposure to water fluoridation.…”
Section: Exclusion Of Modern Methods Of Surveillance Of Water Fluoridmentioning
confidence: 99%
“…Young et al 21 in the United Kingdom found a lower prevalence of caries and lower rates of tooth extractions in children with access to fluoridated drinking water. Also, in New Zealand, another study found some significant differences between Maori and non-Maori children with and without access to fluoridated drinking water 22 .…”
Section: Contemporary Evidencementioning
confidence: 98%